The path to success: career development in equestrian coaching - Wolframm, I.; de Bruijn, S.; Barron, J.; Hoogenboom, A. (Embracing science to enhance equine welfare and horse-human interactions, 2013)
Researchers in coaching science agree that most top sports coaches follow similar "career" paths. They invest many years in their chosen sport, participate in advanced competition themselves, and, at the end of their active careers, pursue a career in coaching. Yet little empirical evidence exists regarding career development in equestrian sports coaching. Thus, this exploratory study aimed to examine a number of relevant factors relating to career paths of equestrian coaches. To that end an online survey was developed and distributed via social media, determining age at first involvement with equestrianism; years active in the sport, highest level ridden at (unofficial/no competitions; amateur sport; talent development squads, national squads, professional), hours spent coaching per week, years as coach, and highest level of coaching achieved (unofficial/no competitions; amateur sport; talent development squads, national squads, professional). The response rate was N=161 (female=140; male=17; unknown=4) from more than 15 countries. Participants` ages ranged from 19 to 70 years, with the largest percentage (28%) in the 31-40 years category. Dressage coaching was represented with 45.3%, while combined dressage and show jumping coaching was carried out by 19.9% of participants, followed by eventing (9.3%), showjumping (5.6%), Western (4.3%), leisure (3.1%), classical dressage (1.9%), long distance (1.2%), vaulting (1.2%) and other (8.1%). Spearman`s Rho correlations were conducted to determine correlations between different variables. Most important results include significant correlations between highest coaching level achieved and highest level ridden at (rs=.61; p<0.001); years active in the sport (rs=.26; p<0.001); years as coach (rs=.23; p<0.005); hours per week spent coaching (rs=.28; p<0.001). Findings support the notion displayed in other sports that active experience and "know-how" of the sport-specific culture through time involved with the sport are important pre-requisites for forging a career in coaching. Further research into elements such as certification or educational background is recommended. Layperson`s paragraph: Findings suggest that more advanced equestrian coaches also have active competitive experience at higher levels, spent longer in the sport and are coaching more hours per week, enabling the continuous development of knowledge and skill.